Lipids, Health, and Behavior. 1997
DOI: 10.1037/10259-005
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiologic relationships and linkage among triglycerides, hypocholesterolemia, and depression.

Abstract: Over the past decade, depressive symptoms have frequently been observed before treatment, in patients with severe primary and familial hypertriglyceridemia (Fallat & Glueck, 1975;Glueck, Tieger, et al., 1993). When triglycerides are normalized, there is usually concomitant and marked improvement in depressive symptoms . We have hypothesized, congruent with the postulations of other investigators (Avellone

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Among patients with affective disorders, investigators demonstrated that diet-and drug-induced reductions in cholesterol and triglyceride levels were coupled with significant decreases in symptoms of depression and reported life stressors. In a later investigation, Glueck et al [55] reported that the greater the mean reduction in triglycerides and cholesterol, the greater the mean percentage reduction on depression scores.…”
Section: Cognitive Functionmentioning
confidence: 92%
“…Among patients with affective disorders, investigators demonstrated that diet-and drug-induced reductions in cholesterol and triglyceride levels were coupled with significant decreases in symptoms of depression and reported life stressors. In a later investigation, Glueck et al [55] reported that the greater the mean reduction in triglycerides and cholesterol, the greater the mean percentage reduction on depression scores.…”
Section: Cognitive Functionmentioning
confidence: 92%
“…MDD has been related both to high and low serum high-density lipoprotein cholesterol (HDL-C) concentrations (Olusi & Fido, 1996 ;Maes et al 1997), and one study has shown a negative association between depressive symptoms and serum HDL-C among women (Horsten et al 1997). There is also evidence for a positive relationship between depression and hypertriglyceridaemia (Glueck et al 1997), although an inverse association between depressive symptoms and serum TG has been reported among women (Lindberg et al 1994). DT have also been associated with BMI and WHR (Wing et al 1991), and depression scores have been associated with greater cardiovascular reactivity to mental stress (Delehanty et al 1991).…”
Section: Introductionmentioning
confidence: 99%